Interindustrial and Interregional Relations in the Economy of the Republic of Buryatia - Piskunov , Evgeny Y. (Economy of Regions, 2025)
Spatial connections play a crucial role in the economic development of a region. Their assessment and monitoring are vital for the success of large-scale investment projects and the formulation of effective management decisions. This article examines the interindustrial connectivity of the economy of the Republic of Buryatia with the Siberian and Far Eastern Federal Okrugs, as well as the rest of Russia. Interindustry multipliers derived from multi-regional input-output models were used as a measure of connectivity. The study draws on data on interregional supplies and the average number of employees across detailed industries for 2014, as well as national input-output tables for 2016. The study found that the economy of Buryatia, due to its scale and several institutional constraints, heavily depends on interregional supplies across most industries. The most critical dependencies are on the supply of agricultural goods and products from the extractive and petrochemical industries from the Siberian Federal Okrug, various types of technological equipment from other regions of Russia, as well as food and metallurgical products from both territories. Buryatia’s industrial enterprises supply food products, pulp and paper goods, textiles and clothing, and non-metallic mineral products. The republic’s economy is particularly connected to sales markets within the Siberian and Far Eastern Federal Okrugs. The advantages and limitations of the data sets used are discussed, and further research avenues are proposed to incorporate adjusted volumes of interregional supplies, accounting for the activities of microenterprises and individual entrepreneurs.